Ineffectiveness of probiotics in preventing recurrence after curative resection for Crohn's disease: a randomised controlled trial with Lactobacillus GG. Issue 3 (1st September 2002) - Prantera, C; Scribano, M L; Falasco, G; Andreoli, A; Luzi, C
Abstract : Background and aims: Experimental studies have shown that luminal bacteria may be involved in Crohn's disease. Probiotics are a possible alternative to antibiotics. The aim of this randomised placebo controlled study was to determine if Lactobacillus GG, given by mouth for one year, could prevent Crohn's recurrent lesions after surgery or to reduce their severity. Methods: Patients operated on for Crohn's disease in whom all of the diseased gut had been removed were randomly allocated to receive 12 billion colony forming units of Lactobacillus or identical placebo for one year. Ileocolonoscopy was performed at the end of the trial or at the onset of symptoms. Endoscopic recurrence was defined as grade 2 or higher of Rutgeerts scoring system. Results: Eight of 45 patients were excluded from the trial (three for non-compliance and five for protocol violations). Clinical recurrence was ascertained in three (16.6%) patients who received Lactobacillus and in two (10.5%) who received placebo. Nine of 15 patients in clinical remission on Lactobacillus (60%) had endoscopic recurrence compared with six of 17 (35.3%) on placebo (p=0.297). There were no significant differences in the severity of the lesions between the two groups. Conclusions: Lactobacillus GG seems neither to prevent endoscopic recurrence at one year nor reduce the severity of recurrent lesions.